Adhesive, laminate, and packaging material
By using a two-component curable adhesive, combining the polyol composition (X) and the polyisocyanate composition (Y), the problem of adhesive delamination at high temperature and high humidity is solved, and higher heat and moisture resistance is achieved, ensuring the stable performance of the laminate and packaging materials.
Patent Information
- Application Number
- CN202280100689.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-04-29
AI Technical Summary
Under high temperature and high humidity conditions, existing adhesives are prone to delamination between the film or metallization layer, resulting in a degradation of the performance of the packaging material.
A two-component curable adhesive consisting of a polyol composition (X) and a polyisocyanate composition (Y) containing specific reaction products (A) and compound (c) to improve heat and moisture resistance of the adhesive.
The adhesive can reduce delamination under high temperature heat treatment (such as cooking) conditions, providing more stable laminate and packaging material properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive and to a laminate and a packaging material each produced using the adhesive. Background Art
[0002] Composite materials produced by laminating metal foils (such as aluminum foil) or metallized films and plastic films (such as polyethylene, polypropylene, poly(vinyl chloride), polyester or nylon) are used as packaging materials for food, medical supplies, cosmetics, commodities, etc. These laminates are produced by appropriately combining various plastic films, metallized films or metal foils according to the characteristics required for each application and bonding them with various adhesives (Patent Documents 1 to 4).
[0003] [Citation List]
[0004] [Patent Document]
[0005] [Patent Document 1]
[0006] Japanese Unexamined Patent Application Publication No. 2000-263682
[0007] [Patent Document 2]
[0008] Japanese Unexamined Patent Application Publication No. 2000-177771
[0009] [Patent Document 3]
[0010] Japanese Unexamined Patent Application Publication No. 2000-154365
[0011] [Patent Document 4]
[0012] Japanese Unexamined Patent Application Publication No. 9-295386 Summary of the invention
[0013] [Technical issues]
[0014] Some packaging materials are filled with contents, such as food and beverages, and then subjected to heat treatment, such as retorting, at high temperature and high humidity. This can lead to delamination between the adhesive and the film or metallization layer.
[0015] In view of such circumstances, an object of the present invention is to provide a two-component curable adhesive (or referred to as a "two-component curable adhesive") and a laminate and a packaging material each produced using the adhesive, wherein the two-component curable adhesive rarely causes delamination even when subjected to high-temperature heat treatment (such as cooking).
[0016] [Solution to the problem]
[0017] The present invention relates to a two-component curable adhesive, which comprises: a polyol composition (X) containing a reaction product (A) of a composition (A'), wherein the composition (A') contains a polyacid (a), a polyol (b) and a compound (c), wherein the compound (c) has a functional group that can react with a carboxyl group or a hydroxyl group and has an alkoxysilyl group; and a polyisocyanate composition (Y).
[0018] The present invention also relates to a laminate comprising: a first substrate, a second substrate, and an adhesive layer for bonding the first substrate and the second substrate together, wherein the adhesive layer is a cured film of the two-component curable adhesive, and to a packaging material comprising the laminate.
[0019] [Beneficial Effects of the Invention]
[0020] The adhesive according to the present invention can be used to provide laminates and packaging materials that rarely cause delamination even when subjected to high-temperature heat treatment such as retorting. DETAILED DESCRIPTION
[0021] [Adhesive]
[0022] The adhesive according to the present invention is a two-component curable adhesive composed of a polyol composition (X) and a polyisocyanate composition (Y). The adhesive according to the present invention is described in detail below.
[0023] [Polyol composition (X)]
[0024] [Reaction product (A)]
[0025] The polyol composition (X) for use in the adhesive according to the present invention contains a reaction product (A) of a composition (A') containing a polyacid (a), a polyol (b) and a compound (c) having a functional group reactive with a carboxyl group or a hydroxyl group and having an alkoxysilyl group.
[0026] The polyacid (a) may be a known compound used for synthesizing polyester polyol. Specific examples of the polyacid (a) include: aliphatic polyacids such as malonic acid, ethylmalonic acid, dimethylmalonic acid, succinic acid, 2,2-dimethylsuccinic acid, succinic anhydride, alkenylsuccinic anhydride, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, maleic anhydride, itaconic acid, dimer acid and trimer acid;
[0027] Alkyl esters of aliphatic polyacids, such as dimethyl malonate, diethyl malonate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, diethyl pimelate, diethyl sebacate, dimethyl fumarate, diethyl fumarate, dimethyl maleate and diethyl maleate;
[0028] Alicyclic polyacids such as 1,1-cyclopentanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, tetrahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, cyclohexane-1,2,4-tricarboxylic acid-1,2-anhydride, bicycloheptene dicarboxylic anhydride (himic acid) and HET anhydride;
[0029] Aromatic polyacids such as phthalic acid, terephthalic acid, isophthalic acid, phthalic anhydride, 1,4-naphthalene dicarboxylic acid, 2,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic anhydride, naphthalene dicarboxylic acid, trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic dianhydride, biphenyl dicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p′-dicarboxylic acid, benzophenone tetracarboxylic acid, benzophenone tetracarboxylic dianhydride, 5-sodium sulfoisophthalate, tetrachlorophthalic anhydride, and tetrabromophthalic anhydride; and
[0030] Methyl esters of aromatic polyacids, such as dimethyl terephthalate and dimethyl 2,6-naphthalene dicarboxylate. These may be used alone or in combination.
[0031] The polyol (b) is also not particularly limited, and may be a difunctional, trifunctional or higher functional alcohol. Examples of difunctional alcohols include: aliphatic diols such as ethylene glycol, diethylene glycol, propylene glycol, 1,3-propylene glycol, 1,2,2-trimethyl-1,3-propylene glycol, 2,2-dimethyl-3-isopropyl-1,3-propylene glycol, 1,4-butanediol, 1,3-butanediol, 3-methyl-1,3-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,4-bis(hydroxymethyl)cyclohexane, 2,2,4-trimethyl-1,3-pentanediol and dimer glycol;
[0032] ether glycols, such as polyethylene glycol and polypropylene glycol;
[0033] Modified polyether diols prepared by ring-opening polymerization of an aliphatic diol and a compound having a cyclic ether bond (such as ethylene oxide, propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether or allyl glycidyl ether);
[0034] Lactone polyester polyols prepared by polycondensation of aliphatic diols and lactones such as lactide or ε-caprolactone;
[0035] Bisphenols, such as bisphenol A and bisphenol F; and
[0036] Alkylene oxide adducts of bisphenols prepared by adding ethylene oxide, propylene oxide, etc. to bisphenols such as bisphenol A or bisphenol F.
[0037] Examples of trifunctional or higher-functional polyols include: aliphatic polyols such as trimethylolethane, trimethylolpropane, glycerol, hexanetriol, and pentaerythritol;
[0038] Modified polyether polyols prepared by ring-opening polymerization of an aliphatic polyol and a compound having a cyclic ether bond (such as ethylene oxide, propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether or allyl glycidyl ether); and
[0039] Lactone polyester polyols are prepared by the polycondensation reaction of aliphatic polyols and lactones (such as ε-caprolactone).
[0040] Examples of the functional group of the compound (c) having a functional group reactive with a carboxyl group or a hydroxyl group and having an alkoxysilyl group include an epoxy group, an amino group and an isocyanate group. For simplicity, the functional group reactive with a carboxyl group or a hydroxyl group of the compound (c) is also referred to as a functional group (c') hereinafter.
[0041] Specific examples of the compound (c) include: compounds (c1) having an amino group and an alkoxysilyl group, such as N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane and N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane;
[0042] Compounds (c2) having an epoxy group and an alkoxysilyl group, such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane and 3-glycidoxypropyltriethoxysilane; and
[0043] Compounds (c3) having an isocyanate group and an alkoxysilyl group, such as 3-isocyanatepropyltriethoxysilane and tris(trimethoxysilylpropyl)isocyanurate.
[0044] The composition (A') contains the polyacid (a) and the polyol (b) such that the molar number of the hydroxyl group in the polyol (b) is much higher than the molar number of the carboxyl group in the polyacid (a).
[0045] The amount of compound (c) in composition (A') can be appropriately adjusted, and is preferably 0.5% by mass or more of composition (A') in terms of more reliable retort resistance. On the other hand, too large a amount of compound (c) may cause the reaction product (A) to have a high viscosity and make it difficult to remove the reaction product (A) from the production device. In terms of production efficiency, the content of compound (c) in composition (A') is preferably 10% by mass or less.
[0046] The hydroxyl value of the reaction product (A) is appropriately adjusted depending on the purpose, and is, for example, 1 mgKOH / g. The hydroxyl value and acid value of the reaction product can be measured by the method described in JIS-K0070.
[0047] The reaction product (A) can be prepared, for example, by polycondensing (esterifying) the composition (A') by conventional methods. More specifically, the composition (A') is charged into a reaction vessel equipped with an agitator and a rectifier and heated to about 130°C under stirring in a pressure range of atmospheric pressure to 0.5 MPa. The water and other substances produced are then evaporated while the temperature is raised at a rate of 5°C / h to 10°C / h in a reaction temperature range of 130°C to 260°C. After 4 to 12 hours of polycondensation reaction, the vacuum is gradually increased from atmospheric pressure to 1 to 300 Torr to evaporate excess polyol (b) and the like and accelerate the reaction.
[0048] For composition (A'), the temperature may be increased after all of the polyacid (a), the polyol (b) and the compound (c) are charged into the reaction vessel, or the temperature may be increased after only the polyol (b) is charged into the reaction vessel, and when the temperature reaches a certain temperature, the polyacid (a) and the compound (c) may be added to start the reaction.
[0049] The catalyst can be used for polycondensation. The polymerization catalyst is preferably composed of at least one metal or a compound of the metal selected from Group 2, Group 4, Group 12, Group 13, Group 14 and Group 15 of the periodic table. Examples of polymerization catalysts composed of such metals or their metal compounds include: metals such as Ti, Sn, Zn, Al, Zr, Mg, Hf and Ge; compounds of these metals, more specifically, titanium tetraisopropoxide, titanium tetrabutoxide, titanium acetylacetonate, stannous octoate, stannous 2-ethylhexanoate, zinc acetylacetonate, zirconium tetrachloride, zirconium tetrachloride tetrahydrofuran complex, hafnium tetrachloride, hafnium tetrachloride tetrahydrofuran complex, germanium oxide and tetraethoxygermanium.
[0050] Preferred examples of commercial polymerization catalysts include Orgatix TA series, TC series, ZA series, ZC series and AL series produced by Matsumoto Fine Chemical Co., Ltd., and organotin catalysts, inorganic metal catalysts and inorganic tin compounds produced by Nitto Kasei Co., Ltd.
[0051] The amount of the polymerization catalyst used is not particularly limited as long as the reaction can be controlled, and the amount of the polymerization catalyst used is, for example, in the range of 10 to 1000 ppm, preferably 20 to 800 ppm, of the total amount of the composition (A'). In order to reduce the coloration of the reaction product (A), the amount of the polymerization catalyst used is more preferably in the range of 30 to 500 ppm.
[0052] The reaction product (A) can be prepared by the above polycondensation reaction and subsequent urethane reaction. The urethane reaction is carried out by heating the polycondensate of the composition (A') and the isocyanate compound (d) at 60 to 100°C, optionally in the presence of a chain extension catalyst and a solvent.
[0053] The isocyanate compound (d) used in the urethane reaction may be, but is not limited to, an aromatic diisocyanate, an aromatic aliphatic diisocyanate, an aliphatic diisocyanate or an alicyclic diisocyanate, or a biuret, a urate, an adduct, an allophanate, a carbodiimide-modified product or a uretdione-modified product thereof. These may be used alone or in combination.
[0054] Examples of aromatic diisocyanates include, but are not limited to, 2,2′-diphenylmethane diisocyanate, 2,4′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate (also known as polymeric MDI or crude MDI), 1,3-phenylene diisocyanate, 4,4′-biphenyl diisocyanate, 1,4-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4′-toluidine diisocyanate, 2,4,6-triisocyanatotoluene, 1,3,5-triisocyanatobenzene, dianisidine diisocyanate, 4,4′-diphenyl ether diisocyanate, and 4,4′,4″-triphenylmethane triisocyanate.
[0055] Aromatic aliphatic diisocyanates refer to aliphatic isocyanates having one or more aromatic rings in the molecule. Examples of aromatic aliphatic diisocyanates include, but are not limited to, m- or p-xylene diisocyanate (also known as XDI) and α,α,α′,α′-tetramethylxylene diisocyanate (also known as TMXDI).
[0056] Examples of aliphatic diisocyanates include, but are not limited to, trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HDI), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0057] Examples of alicyclic diisocyanates include, but are not limited to, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, isophorone diisocyanate (also known as IPDI), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanatomethyl)cyclohexane.
[0058] The low molecular weight polyols used for synthesizing these isocyanate adducts may be known polyols, such as trimethylolpropane.
[0059] The chain growth catalyst may be a known catalyst used as a common carbamate formation catalyst, such as an organic tin compound, an organic carboxylic acid tin salt, a lead carboxylate, a bismuth carboxylate, a titanium compound or a zirconium compound. These may be used alone or in combination. The amount of the chain growth catalyst to be used may be such that the reaction between the polycondensate of the composition (A') and the isocyanate compound (d) is fully promoted, and is preferably, for example, less than 5.0% by mass of the total amount of the polycondensate of the composition (A') and the isocyanate compound (d). The amount of the chain growth catalyst to be used is more preferably less than 1.0% by mass to reduce the hydrolysis or coloring of the resin by the catalyst.
[0060] Examples of good solvents for urethane reactions include methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl ethyl ketone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, toluene and xylene. These may be used alone or in combination.
[0061] The urethane reaction is carried out until substantially all of the isocyanate groups derived from the isocyanate compound (d) used for the reaction are consumed. The residual amount of the isocyanate groups can be determined by measuring the infrared absorption spectrum at 2260 cm -1 It can be determined by checking whether there is an absorption peak in the vicinity (which is an absorption spectrum derived from an isocyanate group), or by measuring the amount of the isocyanate group by titration.
[0062] In addition to the polyester polyol (A1) produced by the esterification reaction of the polyacid (a) and the polyol (b), the polymerization reaction of the composition (A') can also produce various by-products, such as a compound (A2) produced by bonding at least one of the polyacid (a), the polyol (b) and the polyester polyol (A1) to the compound (c) via the functional group (c'), a compound (A3) in which the water produced in the esterification reaction reacts with the compound (c) and hydrolyzes the alkoxysilyl group of the compound (c) into a silanol group, and a polycondensate (A4) of the compound (A3). Therefore, the reaction product (A) is a mixture of these. Unexpectedly, it is clear from the present invention that these by-products contribute to the boiling resistance of the adhesive.
[0063] As is well known, the method of adding a silane coupling agent is a means for improving boiling resistance. However, in this method, when a silane coupling agent is added to a polyol composition (X) and / or a polyisocyanate composition (Y), or when the adhesive is cured, water, isocyanate, etc. in the system react with the alkoxysilyl group of the silane coupling agent, and an alcohol derived from the alkoxysilyl group is produced and retained in the cured film of the adhesive, and can be transferred to the inclusions. In particular, when a silane coupling agent with a methoxy group is used, methanol is retained. Therefore, the adhesive is not preferably used for the production of food packaging materials. On the contrary, according to the present invention, the alcohol derived from the alkoxysilyl group of the compound (c) volatilizes during the polycondensation of the composition (A'). Therefore, the adhesive is unlikely to have such a problem.
[0064] [Polyol (B)]
[0065] In addition to the reaction product (A), the polyol composition (X) may also contain a polyol (B). Examples of polyols (B) include polyester polyols, polyester polyether polyols, polyester polyurethane polyols, polyether polyols, polyether polyurethane polyols, polyurethane polyols, vegetable oil polyols, and polycarbonate polyols. Substances identical or similar to the polyols (b) illustrated above may be used as the raw materials for the reaction product (A).
[0066] The polyacid and the polyol used for synthesizing the polyol having a polyester backbone may be the same as or similar to those exemplified with respect to the polyacid (a) and the polyol (b).
[0067] The isocyanate compound used for synthesizing the polyol having a polyurethane backbone may be the same as or similar to those exemplified with respect to the isocyanate compound (d).
[0068] Examples of the polyether polyol include polyethylene glycol, polypropylene glycol, and a ring-opening polymerization product of an aliphatic polyol and a compound having a cyclic ether bond such as ethylene oxide, propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether or allyl glycidyl ether.
[0069] Examples of the vegetable oil polyol include castor oil, dehydrated castor oil, hydrogenated castor oil (which is a hydrogenation product of castor oil), and an adduct of castor oil with 5 to 50 mol of an alkylene oxide.
[0070] The hydroxyl value of the polyester polyol (B) is appropriately adjusted depending on the purpose, and is, for example, 1 mgKOH / g. The hydroxyl value and acid value of the reaction product can be measured by the method described in JIS-K0070.
[0071] The amount of polyol (B) can be appropriately adjusted. For example, the reaction product (A) accounts for 10% by mass or more of the total amount of the reaction product (A) and the polyol (B). This can more reliably provide an adhesive having high retort resistance.
[0072] When the adhesive according to the present invention is used in the form of a solvent-free adhesive described later, the viscosity of the polyol composition (X) is adjusted to a range suitable for a solvent-free lamination method. For example, the viscosity at 40° C. to 60° C. is adjusted to a range of 100 to 5000 mPas, more preferably 500 to 3000 mPas. The viscosity of the polyol composition (X) can be adjusted, for example, by the main chain and number average molecular weight of the reaction product (A) and the polyol (B) and by the plasticizer (D4) described later.
[0073] [Polyisocyanate composition (Y)]
[0074] The polyisocyanate composition (Y) contains a polyisocyanate compound (C) having a plurality of isocyanate groups. The polyisocyanate compound (C) may be, but is not limited to, an aromatic diisocyanate, an aromatic aliphatic diisocyanate, an aliphatic diisocyanate or an alicyclic diisocyanate, or a biuret, urate, adduct, allophanate, carbodiimide-modified product or uretdione-modified product thereof, or a urethane prepolymer produced by reacting such a polyisocyanate with a polyol. These may be used alone or in combination.
[0075] The aromatic diisocyanate, araliphatic diisocyanate, aliphatic diisocyanate and alicyclic diisocyanate may be those exemplified with respect to the isocyanate compound (d).
[0076] Examples of polyols for synthesizing the urethane prepolymer include those exemplified with respect to the polyol (B).When the urethane prepolymer is used as the polyisocyanate compound (C), at least one of poly(alkylene glycol) and polyester polyol is preferably used to reduce the viscosity and improve the adhesive strength of the adhesive.
[0077] For flexible packaging substrates, it is preferred to use a polyisocyanate prepared by reacting an aromatic polyisocyanate with a poly(alkylene glycol) having a number average molecular weight in the range of 200 to 6000 or a polyisocyanate prepared by reacting an aromatic polyisocyanate with a polyester polyol having a number average molecular weight in the range of 200 to 3000 to impart appropriate flexibility to the cured product. In terms of appropriate resin viscosity and good applicability, those having an isocyanate content in the range of 5% to 20% by mass as measured by titration measurement (using di-n-butylamine) are preferred.
[0078] For hard substrates, polyisocyanates prepared by reacting an aromatic polyisocyanate with a polyester polyol having a number average molecular weight in the range of 200 to 3000 and polyisocyanates prepared by reacting a mixture of an aromatic polyisocyanate, a polyester polyol having a number average molecular weight in the range of 200 to 3000 and a poly(alkylene glycol) having a number average molecular weight in the range of 200 to 6000 are preferred in terms of high adhesive strength. Those having an isocyanate content in the range of 5% to 20% by mass as measured by titration (using di-n-butylamine) are also preferred in terms of appropriate resin viscosity and good applicability.
[0079] When the polyisocyanate compound (C) is a urethane prepolymer, the equivalent ratio [NCO] / [OH] of isocyanate groups to hydroxyl groups in the synthesis reaction is preferably in the range of 1.5 to 5.0 in terms of an adhesive having a viscosity within an appropriate range and high applicability.
[0080] When the adhesive according to the present invention is used in the form of a solvent-free adhesive described later, the viscosity of the polyisocyanate composition (Y) is adjusted to a range suitable for a solvent-free lamination method. For example, the viscosity at 40° C. is adjusted to a range of 500 to 5000 mPas, more preferably 500 to 3000 mPas. The viscosity of the polyisocyanate composition (Y) can be adjusted, for example, by the amount of the urethane prepolymer or the amount of the low molecular weight isocyanate compound.
[0081] [Other components of adhesive (D)]
[0082] Adhesive according to the present invention may contain components other than the above components. Other components (D) may be included in either or both of the polyol composition (X) and the polyisocyanate composition (Y), or may be prepared separately, and immediately after mixing with the polyol composition (X) and the polyisocyanate composition (Y), the adhesive is applied. Each of the components is described below.
[0083] [Catalyst (D1)]
[0084] A metal catalyst, an amine catalyst or an alicyclic amide compound can be used as the catalyst (D1).
[0085] The example of metal catalyst comprises metal complex catalyst, inorganic metal catalyst and organometallic catalyst.The example of metal complex catalyst comprises the acetylacetonate of the metal in the group consisting of Fe (iron), Mn (manganese), Cu (copper), Zr (zirconium), Th (thorium), Ti (titanium), Al (aluminum) and Co (cobalt), such as ferric acetylacetonate, manganese acetylacetonate, copper acetylacetonate and zirconium acetylacetonate.
[0086] Examples of the inorganic metal catalyst include those selected from Sn, Fe, Mn, Cu, Zr, Th, Ti, Al, Co, and the like.
[0087] Examples of the organometallic catalyst include: organozinc compounds such as zinc octoate, zinc neodecanoate and zinc naphthenate; organotin compounds such as stannous diacetate, stannous dioctoate, stannous dioleate, stannous dilaurate, dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin oxide and dibutyltin dichloride; organonickel compounds such as nickel octoate and nickel naphthenate; organocobum compounds such as cobalt octoate and cobalt naphthenate; organobismuth compounds such as bismuth octoate, bismuth neodecanoate and bismuth naphthenate; and titanium compounds such as titanium chelate complexes having as ligands at least one of tetraisopropyloxytitanate, dibutyltitanium dichloride, tetrabutyl titanate, butoxytitanium trichloride, aliphatic diketones, aromatic diketones and alcohols having 2 to 10 carbon atoms.
[0088] Examples of the amine catalyst include triethylenediamine, 2-methyltriethylenediamine, quinuclidine, 2-methylquinuclidine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethylpropylenediamine, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N',N",N"-pentamethyl-(3-aminopropyl)ethylenediamine, N,N,N',N",N"-pentamethyldipropylenetriamine, N,N,N',N'-tetramethylhexamethylenediamine, bis(2-dimethylaminoethyl)ether, dimethylethanolamine, dimethylisopropanolamine, dimethylaminoethoxyethanol, N,N-dimethyl-N'-(2-hydroxyethyl)ethylenediamine, N,N-dimethyl-N'-(2-hydroxyethyl)propylenediamine, bis(dimethylaminopropyl)amine, bis(dimethyl 1-(2-hydroxyethyl)imidazole, 1-(2-hydroxyethyl)imidazole, 1-(2-hydroxypropyl)imidazole, 1-(2-hydroxypropyl)imidazole, 1-(2-hydroxyethyl)imidazole, 1-(2-hydroxypropyl)imidazole, 1-(2-hydroxypropyl)imidazole, 1-(2-hydroxyethyl)imidazole, 1-(2-hydroxypropyl)imidazole, 1-(2-hydroxyethyl)imidazole, 1-(2-hydroxypropyl)imidazole, 1-(2-hydroxyethyl)-2-methylimidazole, and 1-(2-hydroxypropyl)-2-methylimidazole.
[0089] Examples of the alicyclic amide compound include δ-valerolactam, ε-caprolactam, ω-enantholactam, η-capryllactam, and β-propiolactam. Among them, ε-caprolactam is more effective for hardening acceleration.
[0090] [Anhydride (D2)]
[0091] Alicyclic anhydride, aromatic anhydride or unsaturated carboxylic anhydride can be used as anhydride (D2). These can be used alone or in combination. More specifically, examples include: phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, dodecenyl succinic anhydride, poly (adipic anhydride), poly (azelaic anhydride), poly (sebacic anhydride), poly (ethyl octadecane dianhydride), poly (phenyl hexadecane dianhydride), tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, methylbicycloheptene dicarboxylic anhydride (methyl himic anhydride), trialkyltetrahydrophthalic anhydride, methylcyclohexene dicarboxylic anhydride, methylcyclohexene tetracarboxylic anhydride, ethylene glycol ditrimellitic anhydride, HET anhydride, nadic anhydride anhydride), methyl-endimethylenetetrahydrophthalic anhydride, 5-(2,5-dioxotetrahydro-3-furyl)-3-methyl-3-cyclohexane-1,2-dicarboxylic anhydride, 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic anhydride and 1-methyl-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic anhydride.
[0092] Anhydride (D2) can be a diol-modified product of the above-mentioned compound. Examples of diols for modification include: alkylene glycols, such as ethylene glycol, propylene glycol and neopentyl glycol; and poly(ether glycols), such as poly(ethylene glycol), poly(propylene glycol) and poly(tetramethylene ether glycol). Copolymerized polyether glycols of two or more of these diols and / or polyether glycols can also be used.
[0093] [Pigment (D3)]
[0094] Any pigment (D3) can be used, for example, organic pigments and inorganic pigments, such as extender pigments, white pigments, black pigments, gray pigments, red pigments, brown pigments, green pigments, blue pigments, metal powder pigments, luminescent pigments and pearlescent pigments, and plastic pigments, which are described in "Toryo Genryo Binran (Handbook of Raw Materials for Paints)", 1970 (compiled by the Japan Paint Manufacturers Association).
[0095] Examples of extender pigments include: precipitated barium sulfate, chalk, precipitated calcium carbonate, calcium hydrogen carbonate, white limestone, alumina white, silica, fine hydrated silica (white carbon), ultrafine anhydrous silica (Aerosil), quartz sand, talc, precipitated magnesium carbonate, bentonite, clay, kaolin and ochre.
[0096] Specific examples of organic pigments include: insoluble azo pigments such as benzidine yellow, Hansayellow, and Lake Red 4R; soluble azo pigments such as Lake Red C, Carmine 6B, and Bordeaux 10; (copper) phthalocyanine pigments such as phthalocyanine blue and phthalocyanine green; basic dye lakes such as rhodamine lake and methyl violet lake; mordant dye pigments such as quinoline lake and Fast Sky Blue; reduced dye pigments such as anthraquinone pigments, thioindigo pigments, and perinone pigments; quinacridone pigments such as Cinquasia Red B; dioxazine pigments such as dioxazine violet; condensed azo pigments such as Cromophtal; and aniline black.
[0097] Examples of inorganic pigments include: various chromates such as chrome yellow, zinc chromate, and molybdenum chrome orange; various ferrocyanides such as Prussian blue; various metal oxides such as titanium oxide, zinc white, Mapico yellow, iron oxide, colcothar, chromium oxide green, and zirconium oxide; various sulfides and selenides such as cadmium yellow, cadmium red, and mercuric sulfide; various sulfates such as barium sulfate and lead sulfate; various silicates such as calcium silicate and ultramarine blue; various carbonates such as calcium carbonate and magnesium carbonate; various phosphates such as cobalt violet and manganese violet; various metal powder pigments such as aluminum powder, gold powder, silver powder, copper powder, bronze powder, and brass powder; flake pigments of these metals and mica flake pigments; metallic pigments and pearlescent pigments such as mica flake pigments coated with metal oxides and mica iron oxide pigments; and graphite and carbon black.
[0098] Examples of the plastic pigment include "Grandoll PP-1000" and "PP-2000S" produced by DIC Corporation.
[0099] The pigment (D3) to be used can be appropriately selected according to the purpose. For example, in terms of high durability, weather resistance and design properties, it is preferred to use an inorganic oxide such as titanium oxide or zinc white as a white pigment, and it is preferred to use carbon black as a black pigment.
[0100] For example, the amount of the pigment (D3) is in the range of 1 to 400 parts by mass, more preferably 10 to 300 parts by mass, relative to 100 parts by mass of the total solid content of the polyol composition (X) and the polyisocyanate composition (Y), to further improve adhesion and anti-blocking properties.
[0101] [Plasticizer (D4)]
[0102] A phthalic acid plasticizer, a fatty acid plasticizer, an aromatic polyacid plasticizer, a phosphoric acid plasticizer, a polyol plasticizer, an epoxy plasticizer, a polyester plasticizer or a carbonate plasticizer may be used as the plasticizer.
[0103] Examples of phthalic acid plasticizers include phthalate plasticizers such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, diisobutyl phthalate, dihexyl phthalate, diheptyl phthalate, di(2-ethylhexyl)phthalate, di-n-octyl phthalate, dinonyl phthalate, diisononyl phthalate, didecyl phthalate, diisodecyl phthalate, ditridecyl phthalate, diundecyl phthalate, alcohol esters, dilauryl phthalate, distearyl phthalate, diphenyl phthalate, dibenzyl phthalate, butyl benzyl phthalate, dicyclohexyl phthalate, octyl decyl phthalate, dimethyl isophthalate, di(2-ethylhexyl) isophthalate and di(2-octyl) isophthalate; and tetrahydrophthalate plasticizers such as di(2-ethylhexyl) tetrahydrophthalate, di-n-octyl tetrahydrophthalate and di-isodecyl tetrahydrophthalate.
[0104] Examples of fatty acid plasticizers include adipic acid plasticizers such as di-n-butyl adipate, di(2-ethylhexyl) adipate, diisodecyl adipate, diisononyl adipate, di(C6-C10 alkyl) adipate, and dibutyl diglycol adipate. adipate); azelaic acid plasticizers such as di-n-hexyl azelate, di(2-ethylhexyl) azelate and diisooctyl azelate; sebacic acid plasticizers such as di-n-butyl sebacate, di(2-ethylhexyl) sebacate and diisononyl sebacate; maleic acid plasticizers such as dimethyl maleate, diethyl maleate, di-n-butyl maleate and di(2-ethylhexyl) maleate; fumaric acid plasticizers such as di-n-butyl fumarate and di(2-ethylhexyl) fumarate; itaconic acid plasticizers such as monomethyl itaconate, monobutyl itaconate, dimethyl itaconate, diethyl itaconate, dibutyl itaconate and di(2 stearic acid plasticizers such as n-butyl stearate, glyceryl monostearate and diethylene glycol distearate; oleic acid plasticizers such as butyl oleate, glyceryl monooleate and diethylene glycol monooleate; citric acid plasticizers such as triethyl citrate, tri-n-butyl citrate, acetyl triethyl citrate, acetyl tributyl citrate and acetyl tri(2-ethylhexyl) citrate; ricinoleic acid plasticizers such as methyl acetyl ricinoleate, butyl acetyl ricinoleate, glyceryl monoricinoleate and diethylene glycol monoricinoleate; and other fatty acid plasticizers such as diethylene glycol monolaurate, diethylene glycol dipelargonate and pentaerythritol fatty acid esters.
[0105] Examples of the aromatic polyacid plasticizer include trimellitic acid plasticizers such as tri-n-hexyl trimellitate, tri(2-ethylhexyl) trimellitate, tri-n-octyl trimellitate, tri-isooctyl trimellitate, tri-isononyl trimellitate, tri-decyl trimellitate, and tri-isodecyl trimellitate; and pyromellitic acid plasticizers such as tetra(2-ethylhexyl) pyromellitate and tetra-n-octyl pyromellitate.
[0106] Examples of the phosphoric acid plasticizer include triethyl phosphate, tributyl phosphate, tri(2-ethylhexyl) phosphate, tributoxyethyl phosphate, triphenyl phosphate, diphenyl octyl phosphate, diphenyl cresyl phosphate, phenyl cresyl phosphate, tricresyl phosphate, tri(xylene) phosphate, tri(chloroethyl) phosphate, tri(chloropropyl) phosphate, tri(dichloropropyl) phosphate, and tri(isopropylphenyl) phosphate.
[0107] Examples of the polyol plasticizer include glycol plasticizers such as diethylene glycol dibenzoate, dipropylene glycol dibenzoate, triethylene glycol dibenzoate, triethylene glycol di(2-ethylbutyrate), triethylene glycol di(2-ethylhexanoate) and methylenebisthioglycolate dibutyl; and glycerol plasticizers such as glycerol monoacetate, glycerol triacetate and glycerol tributyrate.
[0108] Examples of the epoxy plasticizer include epoxidized soybean oil, epoxy butyl stearate, epoxy hexahydrophthalate di(2-ethylhexyl) phthalate, epoxy hexahydrophthalate diisodecyl phthalate, epoxy triglyceride, epoxidized octyl oleate, and epoxidized decyl oleate.
[0109] Examples of the polyester plasticizer include adipic acid polyester, sebacic acid polyester, and phthalic acid polyester.
[0110] Examples of the carbonate plasticizer include propylene carbonate and ethylene carbonate.
[0111] Other examples of plasticizers include partially hydrogenated terphenyls, adhesion plasticizers, and polymerizable plasticizers such as diallyl phthalate and acrylic monomers and oligomers. These plasticizers may be used alone or in combination.
[0112] [Phosphoric acid compound (D5)]
[0113] Phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) acid phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, lignoceryl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate or polyoxyethylene alkyl ether phosphoric acid can be used as the phosphoric acid compound (D5).
[0114] On the other hand, since the adhesive according to the present invention has high retort resistance, it is preferred not to add a silane coupling agent separately. This can provide an adhesive with less concern about residual alcohol, particularly residual methanol, in the cured film.
[0115] [Adhesive form]
[0116] The adhesive according to the present invention can be a solvent-based adhesive or a solvent-free adhesive. As used herein, the term "solvent-based" adhesive refers to a form used in a dry lamination method, in which the adhesive is applied to a substrate, then heated in an oven or the like to volatilize the organic solvent in the coating film, and then bonded to another base substrate. Either or both of the polyol composition (X) and the polyisocyanate composition (Y) contain an organic solvent capable of dissolving (diluting) the components of the polyol composition (X) and the polyisocyanate composition (Y) used in the present invention.
[0117] Examples of such organic solvents include: esters such as methyl acetate, ethyl acetate, propyl acetate, butyl acetate and cellosolve acetate; ketones such as acetone, methyl ethyl ketone, isobutyl ketone and cyclohexanone; ethers such as tetrahydrofuran and dioxane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as methylene chloride and ethylene dichloride; and dimethyl sulfoxide and dimethylsulfonamide. In some cases, the organic solvent used as a reaction medium in the preparation of the components of the polyisocyanate composition (X) and the polyol composition (Y) can be further used as a diluent for coating.
[0118] As used herein, the term "solvent-free" adhesive refers to an adhesive form used in a solvent-free lamination method, wherein the polyol composition (X) and the polyisocyanate composition (Y) are substantially free of an organic solvent as described above, particularly ethyl acetate or methyl ethyl ketone, and the adhesive is applied to a substrate and then bonded to another substrate without heating in an oven or the like to volatilize the solvent. Even if the organic solvent used as a reaction medium for preparing the components of the polyol composition (X) and the polyisocyanate composition (Y) or their raw materials is not completely removed and is retained in the polyol composition (X) and the polyisocyanate composition (Y) in a very small amount, it is considered that the organic solvent is substantially not included. Low molecular weight alcohol (if present in the polyol composition (X)) reacts with the polyisocyanate composition (Y) and becomes a part of the coating film, so that the low molecular weight alcohol does not need to be volatilized after coating. Therefore, this form is also considered to be a solvent-free adhesive, and the low molecular weight alcohol is not considered to be an organic solvent.
[0119] The adhesive according to the present invention is preferably formulated and used in such a way that the ratio [NCO] / [OH] of the number of moles of isocyanate groups [NCO] in the polyisocyanate composition (Y) to the number of moles of hydroxyl groups [OH] in the polyol composition (X) is in the range of 0.5 to 6.0.
[0120] [Laminate]
[0121] The laminate according to the present invention is prepared by bonding a plurality of substrates (films or papers) by dry lamination or solvent-free lamination using an adhesive according to the present invention. The film is not particularly limited, and the film can be appropriately selected according to the application. For example, for food packaging, the film can be a polyethylene terephthalate (PET) film, a polystyrene film, a polyamide film, a polyacrylonitrile film, a polyolefin film (such as a polyethylene film (LLDPE: low-density polyethylene film, HDPE: high-density polyethylene film, MDOPE: uniaxially stretched polyethylene film, OPE: biaxially stretched polyethylene film) and a polypropylene film (CPP: unstretched polypropylene film, OPP: biaxially stretched polypropylene film)), a polyvinyl alcohol film, and an ethylene-vinyl alcohol copolymer film.
[0122] It is also preferable to use a biomass film formed of a material containing a biomass-derived component. The biomass film is sold by various companies and may be a sheet described in the biomass certified product list of the general incorporated foundation "the Japan Organics Recycling Association".
[0123] More specifically, well-known biomass membranes include films formed by biomass-derived ethylene glycol. Biomass-derived ethylene glycol is prepared by the ethanol (biomass ethanol) produced by biomass. For example, biomass-derived ethylene glycol can be prepared by a method for preparing ethylene glycol by biomass ethanol via ethylene oxide using a known method. Commercial biomass ethylene glycol can also be used. For example, biomass ethylene glycol commercially available from India Glycols Limited can be suitably used.
[0124] For example, as an alternative to conventional polyethylene terephthalate films formed from petroleum raw materials, there are films containing biomass polyester, biomass polyethylene terephthalate, etc., which have biomass-derived ethylene glycol as a diol unit and fossil fuel-derived dibasic acid as a dibasic acid unit.
[0125] The dibasic acid units of the biomass polyester are dibasic acids derived from fossil fuels. The dibasic acid can be any aromatic dibasic acid, aliphatic dibasic acid and derivatives thereof.
[0126] There may also be a copolyester prepared from a copolymer component as a third component in addition to the diol component and the dibasic acid component, such as a difunctional oxycarboxylic acid, or, in order to form a crosslinked structure, at least one polyfunctional compound selected from the group consisting of trifunctional or higher-functional polyols, trifunctional or higher-functional polyacids and / or their anhydrides, and trifunctional or higher-functional oxycarboxylic acids.
[0127] Furthermore, for example, as an alternative to conventional polyolefin films formed from petroleum raw materials, there are biomass polyolefin films such as biomass polyethylene films and biomass polyethylene-polypropylene films containing a polyethylene resin made from biomass-derived ethylene glycol.
[0128] There are no particular restrictions on the polyethylene resin, provided that biomass-derived ethylene glycol is used as a raw material, and the polyethylene resin may be an ethylene homopolymer or a copolymer of ethylene and α-olefins (ethylene-α-olefin copolymers containing 90% by mass or more of ethylene units) mainly composed of ethylene. These may be used alone or in combination.
[0129] The alpha-olefin constituting the copolymer of ethylene and alpha-olefin can be but not limited to the alpha-olefin with 4 to 8 carbon atoms, such as 1-butene, 4-methyl-1-pentene, 1-hexene or 1-octene. Known polyethylene resins can be used, such as low-density polyethylene resins, medium-density polyethylene resins and linear low-density polyethylene resins. Among these resins, in order to further reduce damage, such as perforation and rupture, even when the film is rubbed against each other, linear low-density polyethylene resins (LLDPE) (copolymer of ethylene and 1-hexene or copolymer of ethylene and 1-octene) are also preferred, and density is between 0.910 and 0.925 g / cm3 The linear low-density polyethylene resin within the range is more preferred.
[0130] Biofilms formed from biomass feedstock classified according to the biomass plastic content specified in ISO 16620 or ASTM D 6866 are also distributed. In the atmosphere, radiocarbon 14C is present at a concentration of 1 / 10 12 The ratio of carbon to carbon 14C exists. This ratio does not change in atmospheric carbon dioxide and in plants that fix carbon dioxide through photosynthesis. Therefore, the carbon of plant-derived resins includes radioactive carbon 14C. In contrast, the carbon of fossil fuel-derived resins includes almost no radioactive carbon 14C. Therefore, the plant-derived resin content (i.e., the biomass plastic content of the resin) can be determined by measuring the concentration of radioactive carbon 14C in the resin with an accelerator mass spectrometer.
[0131] Examples of plant-derived low-density polyethylene having a biomass plastic content of 80% or more, preferably 90% or more, as specified in ISO 16620 or ASTM D 6866 include trade names "SBC818", "SPB608", "SBF0323HC", "STN7006", "SEB853" and "SPB681" produced by Braskem. Films made from these raw materials can be appropriately used.
[0132] Films and sheets formed from biomass raw materials starch and polylactic acid are also known. These can be appropriately selected and used according to the intended use.
[0133] The biomass membrane may be a laminate of a plurality of biomass membranes or a laminate of a conventional petroleum membrane and a biomass membrane. These biomass membranes may be unstretched membranes or stretched membranes and may be prepared by any method.
[0134] The film may be stretched. In a typical stretching method, a resin is melt-extruded by an extrusion method or the like to form a sheet, and the sheet is subjected to simultaneous biaxial stretching or sequential biaxial stretching. Sequential biaxial stretching generally includes longitudinal stretching and then transverse stretching. More specifically, longitudinal stretching utilizing a speed difference between rollers and transverse stretching using a tenter are generally used in combination.
[0135] If necessary, the film surface may be subjected to a surface treatment such as a flame treatment or a corona discharge treatment to form an adhesive layer free from defects such as film breakage and cracks.
[0136] Alternatively, a film having a vapor-deposited layer formed of a metal such as aluminum or a metal oxide such as silicon dioxide or aluminum oxide may be used, or a barrier film having a gas barrier layer formed of poly(vinyl alcohol), ethylene-vinyl alcohol copolymer, or polyvinylidene chloride may be used. Such a film can be used to produce a laminate having barrier properties against water vapor, oxygen, alcohol, inert gas, volatile organic substances (fragrance), etc.
[0137] The paper can be any known paper substrate. More specifically, paper is produced from natural fibers for papermaking (such as wood pulp) using known paper machines under any papermaking conditions. Examples of natural fibers for papermaking include wood pulp (such as softwood pulp and hardwood pulp), non-wood pulp (such as abaca pulp, sisal pulp and flax pulp) and chemically modified pulps thereof. Examples of pulp include chemical pulps produced by sulfate cooking, acid / neutral / alkaline sulfite cooking or soda cooking, ground pulp, chemically ground pulp and thermomechanical pulp. Various types of commercial high-quality papers, coated papers, backing papers, impregnated papers, cardboard, paperboard, etc. can also be used.
[0138] The laminate produced using the adhesive according to the present invention has high resistance to boiling. Therefore, this laminate can certainly be suitable for general applications, and in particular for applications involving boiling. The specific structure includes, but is not limited to: transparent vapor-deposited Ny film / adhesive layer / sealant film, transparent vapor-deposited PET film / adhesive layer / sealant film, transparent vapor-deposited PET film / adhesive layer / sealant film, transparent vapor-deposited PET film / adhesive layer / Ny film / adhesive layer / sealant film, OPP film / adhesive layer / transparent vapor-deposited PET film / adhesive layer / sealant film, Ny film / adhesive layer / transparent vapor-deposited PET film / adhesive layer / sealant film, PET film / adhesive layer / transparent vapor-deposited PET film / adhesive layer / sealant film, transparent vapor-deposited Ny film / adhesive layer / transparent vapor-deposited PET film / adhesive layer / sealant film, and transparent vapor-deposited PET film / adhesive layer / transparent vapor-deposited PET film / adhesive layer / sealant film. Aluminum metallized film can also be used instead of transparent vapor-deposited film.
[0139] In such a laminate comprising a plurality of adhesive layers, the adhesive according to the present invention is preferably used for the adhesive layer in contact with the transparent vapor deposited layer and the aluminum metallized layer. Although steaming generally causes delamination, especially delamination between the transparent vapor deposited layer and the adhesive layer or between the aluminum metallized layer and the adhesive layer, the use of the adhesive according to the present invention can reduce such problems. The other adhesive layers can be bonded with the adhesive according to the present invention or with a general-purpose urethane adhesive as long as there are no particular problems. Although the laminate for packaging materials is generally provided with a printed layer described below at an appropriate position, the printed layer is omitted in the above example.
[0140] In the laminate according to the present invention, the printing layer may be provided between the adhesive layer and the substrate (generally the substrate used as the outermost layer of the inclusions). The printing layer is formed by a general printing method for printing on a film, using printing inks such as gravure printing inks, flexographic printing inks, lithographic printing inks, stencil inks or inkjet inks.
[0141] The solvent-based adhesive according to the present invention is applied to one substrate using a roller (such as a gravure roller), heated in an oven or the like to volatilize the organic solvent, and then bonded to another substrate to produce a laminate according to the present invention. Lamination is preferably followed by aging. The aging temperature is preferably in the range of room temperature to 80° C., and the aging time is preferably in the range of 12 to 240 hours.
[0142] The solvent-free adhesive according to the present invention is preheated to about 40° C. to 100° C., applied to one substrate using a roller (such as a coating roller), and then immediately bonded to another substrate to produce a laminate according to the present invention. Lamination is preferably followed by aging. The aging temperature is preferably in the range of room temperature to 70° C., and the aging time is preferably in the range of 6 to 240 hours.
[0143] The amount of adhesive applied is appropriately adjusted. The solid content of the solvent-based adhesive is adjusted to, for example, 1 g / m 2 Above and 10 g / m 2 Below, preferably 2 g / m 2 Above and 5 g / m 2 The coating amount of the solvent-free adhesive is, for example, 1 g / m 2 Above and 5 g / m 2 Below, preferably 1 g / m 2 Above and 3.5 g / m 2 the following.
[0144] Laminate according to the present invention comprises two base materials bonded together with adhesive according to the present invention, and may comprise another base material as required.Another base material can be combined by known methods, for example dry lamination, solvent-free lamination, hot lamination, heat sealing or extrusion lamination.The adhesive used in this case may or may not be adhesive according to the present invention.Another base material may be the base material described above.
[0145] [Packaging materials]
[0146] The packaging material according to the present invention is produced by forming the above-mentioned laminate into a bag and heat-sealing the bag. The packaging material may be in the form of a three-side sealed bag, a four-side sealed bag, a gusseted bag, a pillow bag, a gable top bottomed vessel, a Tetra Classic, a brick type, a tube container, a paper cup or a lid material. The packaging material according to the present invention may be appropriately subjected to easy opening treatment or have a resealing device.
[0147] The packaging material according to the present invention can be used industrially as a packaging material mainly for food, detergents and medicines. Specific applications include detergents and medicines, such as liquid laundry detergents, liquid kitchen detergents, liquid bathroom detergents, liquid bath soaps, liquid shampoos, liquid conditioners and pharmaceutical tablets. The packaging material according to the present invention can also be used as a secondary packaging material for the above containers.
[0148] [Example]
[0149] Although the present invention is described in more detail in the following specific examples and synthesis examples, the present invention is not limited to these examples. In the following examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "mass %", respectively.
[0150] [Polyol composition (X)]
[0151] [Reaction product (A-1)]
[0152] Under nitrogen, 7.2 parts of ethylene glycol, 15.8 parts of diethylene glycol, 22.5 parts of neopentyl glycol, 21.9 parts of adipic acid, 4.6 parts of sebacic acid, 28.0 parts of isophthalic acid and 1.3 parts of KBM-403 (3-glycidyloxypropyltrimethoxysilane, produced by Shin-Etsu Chemical Co., Ltd.) were loaded into a reaction vessel equipped with an agitator, a thermometer, a nitrogen inlet pipe, a rectifying tower and a water separator. During the dehydration reaction, the mixture was gradually heated to 250°C in a nitrogen stream at atmospheric pressure, and it was reacted at 250°C for 2 hours. When the mixture became transparent and the temperature at the top of the rectifying tower reached 80°C or lower, the temperature was reduced to 240°C, the rectifying tower was switched to a condenser, and the pipeline was connected to a vacuum pump. The reaction was continued under reduced pressure in the range of 30 to 60 Torr to reach a predetermined acid value and viscosity. Thus, a reaction product (A-1) was prepared.
[0153] The reaction product (A-1) had an acid value of 0.7 mgKOH / g and a hydroxyl value of 159.0 mgKOH / g.
[0154] [Reaction product (A-2)]
[0155] Under nitrogen, 7.2 parts of ethylene glycol, 15.8 parts of diethylene glycol and 22.5 parts of neopentyl glycol were loaded into a reaction vessel equipped with an agitator, a thermometer, a nitrogen inlet pipe, a rectifying tower and a water separator, and the mixture was melted by heating under stirring. Subsequently, 21.9 parts of adipic acid, 4.6 parts of sebacic acid, 28.0 parts of isophthalic acid and 6.8 parts of KBM-403 were loaded at 120°C to 130°C. During the dehydration reaction, the mixture was gradually heated to 240°C under a pressure of about 0.5 MPa, and the pressure was reduced when the temperature reached 240°C. When the mixture became transparent and the temperature at the top of the rectifying tower reached 80°C or lower, the rectifying tower was switched to a condenser, and a pipeline was connected to a vacuum pump. The reaction was continued under reduced pressure within the range of 30 to 60 Torr to reach a predetermined acid value and viscosity. Thus, a reaction product (A-2) was prepared.
[0156] The reaction product (A-2) had an acid value of 0.6 mgKOH / g and a hydroxyl value of 154.0 mgKOH / g.
[0157] [Reaction product (A-3)]
[0158] Under nitrogen, 7.2 parts of ethylene glycol, 15.8 parts of diethylene glycol and 22.5 parts of neopentyl glycol were charged into a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet pipe, a distillation tower and a water separator, and the mixture was melted by heating under stirring. Subsequently, 21.9 parts of adipic acid, 4.6 parts of sebacic acid, 28.0 parts of isophthalic acid and 3.2 parts of KBE-903 (3-aminopropyltriethoxysilane, produced by Shin-Etsu Chemical Co., Ltd.) were charged at 120° C. to 130° C. The mixture was gradually heated to 250° C. in a nitrogen stream at atmospheric pressure during the dehydration reaction, and was reacted at 250° C. for 2 hours. When the mixture became transparent and the temperature at the top of the distillation tower reached 80° C. or less, the temperature was reduced to 230° C., and xylene was added to promote the dehydration reaction at the same temperature, while the xylene was refluxed using a water separator. When the acid value is reduced to less than 5.0 mgKOH / g, the distillation column is switched to a condenser and the pipeline is connected to a vacuum pump. While removing xylene under reduced pressure in the range of 30 to 60 Torr, the reaction is continued to reach a predetermined acid value and viscosity. Thus, a reaction product (A-3) is prepared.
[0159] The reaction product (A-3) had an acid value of 0.8 mgKOH / g and a hydroxyl value of 156.0 mgKOH / g.
[0160] [Reaction product (A-4)]
[0161] Under nitrogen, 14.0 parts of ethylene glycol and 20.9 parts of neopentyl glycol were loaded into a reaction vessel equipped with an agitator, a thermometer, a nitrogen inlet pipe, a distillation tower and a water separator, and the mixture was melted by heating under stirring. Subsequently, 24.3 parts of adipic acid, 20.4 parts of isophthalic acid, 20.4 parts of terephthalic acid and 1.0 part of KBM-403 were loaded at 120°C to 130°C. The mixture was gradually heated to 260°C under a pressure of about 0.5 MPa during the dehydration reaction, and the pressure was reduced when the temperature reached 260°C. When the mixture became transparent and the temperature at the top of the distillation tower reached 80°C or less, the temperature was reduced to 230°C, and xylene was added to promote the dehydration reaction at the same temperature, while the water separator was used to reflux the xylene. When the acid value was reduced to less than 5.0 mgKOH / g, the distillation tower was switched to a condenser, and the pipeline was connected to a vacuum pump. While removing xylene under reduced pressure in the range of 30 to 60 Torr, the reaction was continued to achieve a predetermined acid value and viscosity. Thus, an intermediate of the reaction product (A-4) was prepared.
[0162] The intermediate of the reaction product (A-4) had an acid value of 1.2 mgKOH / g and a hydroxyl value of 27.0 mgKOH / g.
[0163] Into a reaction vessel equipped with an impeller blade, a temperature sensor, a nitrogen inlet pipe and a condenser pipe, 97.0 parts of an intermediate of the reaction product (A-4), 53.8 parts of ethyl acetate and 0.02 parts of a polymerization catalyst dibutyltin dilaurate were loaded. After the mixture was heated to 60°C in a nitrogen stream at atmospheric pressure, 3.0 parts of isophorone diisocyanate were added to the mixture. The mixture was heated to 80°C and a carbamate reaction was carried out at 80°C. After reaching a predetermined viscosity and the residual isocyanate content being less than 0.05%, the temperature was reduced to 50°C, and the non-volatile content was adjusted with ethyl acetate. Thus a reaction product (A-4) was prepared.
[0164] The reaction product (A-4) had an acid value of 1.1 mgKOH / g based on the solid content, a hydroxyl value of 11.9 mgKOH / g based on the solid content, and a non-volatile matter content of 65.0%.
[0165] [Reaction product (A-5)]
[0166] Under nitrogen, 14.0 parts of ethylene glycol and 20.9 parts of neopentyl glycol are loaded into a reaction vessel equipped with an agitator, a thermometer, a nitrogen inlet pipe, a rectifying tower and a water separator, and the mixture is melted by heating under stirring. Subsequently, 24.3 parts of adipic acid, 20.4 parts of isophthalic acid, 20.4 parts of terephthalic acid and 1.0 part of KBM-403 are loaded at 120 ℃ to 130 ℃. During the dehydration reaction, the mixture is gradually heated to 260 ℃ under a pressure of about 0.5 MPa, and the pressure is reduced when the temperature reaches 260 ℃. When the mixture becomes transparent and the temperature at the top of the rectifying tower reaches 80 ℃ or lower, the temperature is reduced to 240 ℃, the rectifying tower is switched to a condenser, and the pipeline is connected to a vacuum pump. The reaction is continued under reduced pressure within the range of 30 to 60 Torr to obtain a predetermined acid value and viscosity. Thus an intermediate of reaction product (A-5) is prepared.
[0167] The intermediate of the reaction product (A-5) had an acid value of 0.8 mgKOH / g and a hydroxyl value of 26.2 mgKOH / g.
[0168] Into a reaction vessel equipped with an impeller blade, a temperature sensor, a nitrogen inlet pipe and a condenser pipe, 97.0 parts of an intermediate of the reaction product (A-5), 53.8 parts of ethyl acetate and 0.02 parts of a polymerization catalyst dibutyltin dilaurate were loaded. After the mixture was heated to 60°C in a nitrogen stream at atmospheric pressure, 3.0 parts of isophorone diisocyanate were added to the mixture. The mixture was heated to 80°C and a carbamate reaction was carried out at 80°C. After reaching a predetermined viscosity and the residual isocyanate content being less than 0.05%, the temperature was reduced to 50°C, and the non-volatile content was adjusted with ethyl acetate. Thus a reaction product (A-5) was prepared.
[0169] The reaction product (A-5) had an acid value of 0.8 mgKOH / g based on the solid content, a hydroxyl value of 11.0 mgKOH / g based on the solid content, and a non-volatile matter content of 65.0%.
[0170] [Reaction product (AH-1)]
[0171] Under nitrogen, 7.2 parts of ethylene glycol, 15.8 parts of diethylene glycol, 22.5 parts of neopentyl glycol, 21.9 parts of adipic acid, 4.6 parts of sebacic acid and 28.0 parts of isophthalic acid were charged into a reaction vessel equipped with an agitator, a thermometer, a nitrogen inlet pipe, a distillation tower and a water separator. During the dehydration reaction, the mixture was gradually heated to 250° C. in a nitrogen stream at atmospheric pressure and reacted at 250° C. for 2 hours. When the mixture became transparent and the temperature at the top of the distillation tower reached 80° C. or lower, the temperature was reduced to 240° C., the distillation tower was switched to a condenser, and the pipeline was connected to a vacuum pump. The reaction was continued under reduced pressure in the range of 30 to 60 Torr to obtain a predetermined acid value and viscosity. Thus, a reaction product (AH-1) was prepared.
[0172] The reaction product (AH-1) had an acid value of 1.3 mgKOH / g and a hydroxyl value of 168.0 mgKOH / g.
[0173] [Reaction product (AH-2)]
[0174] Under nitrogen, 14.0 parts of ethylene glycol and 20.9 parts of neopentyl glycol were loaded into a reaction vessel equipped with an agitator, a thermometer, a nitrogen inlet pipe, a distillation tower and a water separator, and the mixture was melted by heating under stirring. Subsequently, 24.3 parts of adipic acid, 20.4 parts of isophthalic acid and 20.4 parts of terephthalic acid were loaded at 120°C to 130°C. The mixture was gradually heated to 260°C under a pressure of about 0.5 MPa during the dehydration reaction, and the pressure was reduced when the temperature reached 260°C. When the mixture became transparent and the temperature at the top of the distillation tower reached 80°C or less, the temperature was reduced to 230°C, and xylene was added to promote the dehydration reaction at the same temperature, while the water separator was used to reflux the xylene. When the acid value was reduced to less than 5.0 mgKOH / g, the distillation tower was switched to a condenser, and the pipeline was connected to a vacuum pump. While removing xylene under reduced pressure in the range of 30 to 60 Torr, the reaction was continued to achieve a predetermined acid value and viscosity, thereby preparing a reaction product (AH-2').
[0175] The reaction product (AH-2') had an acid value of 1.3 mgKOH / g and a hydroxyl value of 27.0 mgKOH / g.
[0176] 97.0 parts of reaction product (AH-2'), 53.8 parts of ethyl acetate and 0.02 parts of polymerization catalyst dibutyltin dilaurate were loaded into a reaction vessel equipped with impeller blades, a temperature sensor, a nitrogen inlet pipe and a condenser pipe. After the mixture was heated to 60°C in a nitrogen stream at atmospheric pressure, 3.0 parts of isophorone diisocyanate were added to the mixture. The mixture was heated to 80°C and a urethane reaction was carried out at 80°C. After reaching a predetermined viscosity and the residual isocyanate content was less than 0.05%, the temperature was reduced to 50°C and the non-volatile content was adjusted with ethyl acetate. Thus a reaction product (AH-2) was prepared.
[0177] The reaction product (AH-2) had an acid value of 1.3 mgKOH / g based on solid content, a hydroxyl value of 13.1 mgKOH / g based on solid content, and a non-volatile content of 65.0%.
[0178] The reaction products (A-1) to (A-5), (AH-1), (AH-2), KBM-403 and KBE-903 were mixed in the amounts (solid contents) shown in Tables 1 and 2 to prepare polyol compositions (X) of Examples and Comparative Examples.
[0179] [Polyisocyanate composition (Y)]
[0180] [Polyisocyanate compound (C-1)]
[0181] Commercially available uric acid ester of isophorone diisocyanate and uric acid ester of hexamethylene diisocyanate were mixed at a ratio of 1:4 parts by weight to prepare a polyisocyanate composition (C-1).
[0182] [Polyisocyanate compound (C-2)]
[0183] A trifunctional polyisocyanate prepared by adding toluene diisocyanate to trimethylolpropane (product name: DICDRY KW-75, produced by DIC Corporation, solid content: 75%) was used as the polyisocyanate composition (C-2).
[0184] [Preparation of adhesive]
[0185] Reactive adhesives for Examples and Comparative Examples were prepared by mixing the reaction product (A), the polyisocyanate compound (C) and the silane coupling agent in the ratios shown in Tables 3 and 4. Ethyl acetate was used as a solvent to adjust the viscosity as necessary.
[0186] [Preparation of Laminated Body]
[0187] The adhesive was adjusted to 3.2 g / m 2The adhesive was applied in an amount of 100 μm to the vapor-deposited surface of a PET film (Techbarrier L, produced by Mitsubishi Chemical Corporation) on which silicon dioxide was deposited, and then the adhesive-coated surface was bonded to a LLDPE film (linear low-density polyethylene film TUX(TM) HC, produced by Mitsui Chemicals Tohcello, Inc.) having a thickness of 60 μm. The film was aged at 40° C. for 4 days to prepare a laminate for evaluation.
[0188] [evaluate]
[0189] [Residual alcohol content]
[0190] The residual alcohol content of the solid component of each polyol composition (X) used in the examples and comparative examples was determined by 13C-NMR measurement under the following conditions. Methanol was added to the model resin in advance, and the detection limit of methanol was determined in the same manner as the polyol composition (X). Based on the detection limit of methanol, the residual alcohol content was evaluated into the following two levels.
[0191] O: less than 0.1% by weight (undetectable)
[0192] X: 0.1 wt% or more
[0193] [Study of detection limit using model resin (MeOH addition)]
[0194] 750 mg of the binder model 1), 2) or 3) mixed as described below was weighed and dissolved in 250 μl of deuterated chloroform to prepare a measurement sample.
[0195] 1) Adhesive without silane coupling agent: MeOH = 99.9: 0.1 wt%
[0196] 2) Adhesive without silane coupling agent: MeOH = 99.7: 0.3 wt%
[0197] 3) Adhesive without silane coupling agent: MeOH = 99.5: 0.5 wt%
[0198] [sample]
[0199] 750 mg of the sample was dissolved in 250 μl of deuterated chloroform to prepare a measurement sample.
[0200] [NMR measurement conditions]
[0201] Apparatus: ECX-400P manufactured by JEOL Ltd.
[0202] Measuring temperature: room temperature
[0203] Resonance frequency: 100 MHz
[0204] Nuclides / parameters measured: 13C-NMR (fully decoupled) / scan 1000, relaxation delay 2 s, flip angle 30 degrees, x_offset 100 ppm, x_scan 250 ppm, x_point 32768.
[0205] [Adhesion strength]
[0206] The laminate was cut into test pieces of 300 mm in length and 15 mm in width. The 180 degree peel strength (N / 15 mm) between the silica deposited PET film and the LLDPE film was measured at a width of 15 mm using an Instron type tensile tester at 25°C at a peel rate of 300 mm / min.
[0207] [Retort resistance]
[0208] The laminate for evaluation was cut into a size of 150 mm × 300 mm and bent so that the LLDPE film was inside. Both sides of the laminate were heat sealed at 1 atm, 180°C for 1 second to prepare a pouch. The pouch was filled with 1 / 1 / 1 sauce (meat sauce: vegetable oil: vinegar = 1:1:1). The remaining sides of the pouch were heat sealed under the same conditions to completely seal the pouch. The filled pouch was immersed in 98°C hot water for retort sterilization for one hour. The pouch from which the contents had been taken out was opened and cut into strips with a width of 15 mm to prepare a test piece. The 180-degree peel strength (N / 15 mm) between the PET film deposited with silica and the LLDPE film was measured at a peel rate of 300 mm / min at 25°C using an Instron type tensile tester at a width of 15 mm. The test piece that caused delamination at the completion of retort sterilization was indicated as "delamination" and no peel strength measurement was performed.
[0209] [Table 1]
[0210]
[0211] [Table 2]
[0212]
[0213] [Table 3]
[0214]
[0215] [Table 4]
[0216]
Claims
1. A two-component curable adhesive, the two-component curable adhesive comprising: A polyol composition (X) comprising a reaction product (A) of a composition (A') comprising a polyacid (a), a polyol (b), and a compound (c) having a functional group reactive with a carboxyl group or a hydroxyl group and having an alkoxysilyl group; and Polyisocyanate composition (Y). 2 . The two-component curable adhesive according to claim 1 , wherein the compound (c) accounts for 0.5% by mass or more and 10% by mass or less of the composition (A′). 3 . The two-component curable adhesive according to claim 1 , wherein the polyol composition (X) comprises a polyol (B).
4. The two-component curable adhesive according to any one of claims 1 to 3, wherein The composition (A') contains a polyisocyanate (d), and The reaction product (A) is a reaction product of the polyisocyanate (d) and a reaction product of the polyacid (a), the polyol (b) and the compound (c).
5. The two-component curable adhesive according to any one of claims 1 to 4, wherein the functional group reactive with a carboxyl group or a hydroxyl group is an amino group.
6. The two-component curable adhesive according to any one of claims 1 to 4, wherein the functional group reactive with a carboxyl group or a hydroxyl group is an epoxy group.
7. A laminate, comprising: a first substrate; a second substrate; as well as an adhesive layer between the first substrate and the second substrate, The adhesive layer is a cured film of the two-component curable adhesive according to any one of claims 1 to 6.
8. A packaging material comprising the laminate according to claim 7.